Assessment of Dietary Intake, Nutritional Status, and Cardiovascular Risk in University Students - Zazuelta-Valenzuela, David Alfonso; Leyva Camacho, Lucia; Retamoza Rubio, Astrid Aimeé; Paz Cassini, Mariela; Rendon Delcid, Pablo Alejandro (Health Nexus, 2026)
This study assessed the eating habits, nutritional status, and cardiovascular risk in university students. The sample consisted of 295 new students (188 female, 107 male) who attended the induction week at the Autonomous University of Occident and met the inclusion criteria: being adults, enrolled in any undergraduate degree offered by the university, and agreeing to participate through informed consent. The data collection consisted of two parts: an initial survey to collect general characteristics and self-reported height and weight, and the measurement of waist and hip circumferences according to the ISAK protocol. Then, a short version of the FFQ was applied to collect dietary information. Data was captured on MS Excel, and mean, standard deviation, frequencies, and 95 % confidence intervals were reported. Statistical tests were analyzed using SPSS version 26. Results: 38 % of the students are overweight or obese, being higher in men (42 % vs 35.6 % in women). 7.35 % of women and 10.96 % of men presented high WHR, and 33.09 % of women and 35.62 % of men presented high WHRt. Low weekly consumption was found in dairy products (7.13 CI 95 % 6.71 - 7.56), vegetables (5.83 CI 95 % 5.33 - 6.34), and fruits (6.92 CI 95 % 6.43 – 7.42). Processed foods and junk food are highly consumed (8.77 CI 95 % 8.10 - 9.45, and 14.20 CI 95 % 13.20 – 15.20, respectively). Significant correlations were found on weekly consumption of processed foods and junk food (R = 0.765, p < 0.001), processed foods and dairy products (R = 0.436, p